Code-Switching Practices in Multilingual Classrooms: Exploring Pedagogical Functions - Hafid Hafid; Margana Margana (STAI Hubbulwathan Duri, 2022)
This study explored the pedagogical functions of code-switching toward teaching and learning processes in multilingual classrooms. The pedagogical function is strongly important to be recognized regarding the successfulness and effectiveness of teaching and learning process. This study reports on code-switching practices for multilingual classroom communication in secondary level in Indonesia, which English is the main instruction of teaching. This study employed ethnographic case study design and the data were gathered through observation, interview and recording. The data were analyzed using qualitative descriptive and the obtained data demonstrated that code-switching has three function categories in terms of pedagogical functions, i.e. 1) knowledge construction/curriculum access, 2) classroom management, and 3) interpersonal relationship. If so, teachers and students are allowed to switch their language as long as they fulfill academic functions and expand students’ language repertoire. It can be inferred that the findings suggested that these practices could foster students to become bilingual people and promote the language minority.